Evaluation of Neonatal Screening Programs for Tyrosinemia Type 1 Worldwide - Allysa M. Kuypers; Marelle J. Bouva; J. Gerard Loeber; Anita Boelen; Eugenie Dekkers; Konstantinos Petritis; C. Austin Pickens; The ISNS Representatives; Francjan J. van Spronsen; M. Rebecca Heiner-Fokkema (International Journal of Neonatal Screening)
In The Netherlands, newborn screening (NBS) for tyrosinemia type 1 (TT1) uses dried blood spot (DBS) succinylacetone (SUAC) as a biomarker. However, high false-positive (FP) rates and a false-negative (FN) case show that the Dutch TT1 NBS protocol is suboptimal. In search of optimization options, we evaluated the protocols used by other NBS programs and their performance. We distributed an online survey to NBS program representatives worldwide (N = 41). Questions focused on the organization and performance of the programs and on changes since implementation. Thirty-three representatives completed the survey. TT1 incidence ranged from 1/13,636 to 1/750,000. Most NBS samples are taken between 36 and 72 h after birth. Most used biomarkers were DBS SUAC (78.9%), DBS Tyrosine (Tyr; 5.3%), or DBS Tyr with second tier SUAC (15.8%). The pooled median cut-off for SUAC was 1.50 µmol/L (range 0.3–7.0 µmol/L). The median cut-off from programs using laboratory-developed tests was significantly higher (2.63 µmol/L) than the medians from programs using commercial kits (range 1.0–1.7 µmol/L). The pooled median cut-off for Tyr was 216 µmol/L (range 120–600 µmol/L). Overall positive predictive values were 27.3% for SUAC, 1.2% for Tyr solely, and 90.1% for Tyr + SUAC. One FN result was reported for TT1 NBS using SUAC, while three FN results were reported for TT1 NBS using Tyr. The NBS programs for TT1 vary worldwide in terms of analytical methods, biochemical markers, and cut-off values. There is room for improvement through method standardization, cut-off adaptation, and integration of new biomarkers. Further enhancement is likely to be achieved by the application of post-analytical tools.